2012
DOI: 10.1007/s13193-012-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer: A Clinicopathologic Study of 42 Patients in Eastern India

Abstract: Retrospective review of presentation, treatment and outcome of male breast cancer in a tertiary cancer centre in eastern India. Data of 42 male breast cancer (MBC) patients, who presented between April, 2001 and March, 2008 were collected from institute records with respect to epidemiological characteristics, clinical and pathological parameters, treatment pattern and outcome. This series includes 42 patients with mean age of 56 years (range 31-78 years). MBC represented 1.1 % of all breast cancer. History o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…(Kaushik et al, 2014) Most Western studies have reported a 5 year OS of greater than 60% whereas results of Asian and African countries have shown a 5 year OS ranging from 40-60%. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Sedighi et al, 2013) Our 5 year OS was 61.1% which was consistent with most of the South Asian studies as well as Western studies.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…(Kaushik et al, 2014) Most Western studies have reported a 5 year OS of greater than 60% whereas results of Asian and African countries have shown a 5 year OS ranging from 40-60%. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Sedighi et al, 2013) Our 5 year OS was 61.1% which was consistent with most of the South Asian studies as well as Western studies.…”
Section: Discussionsupporting
confidence: 87%
“…This can be attributed to factors such as lack of screening mammography and public awareness. (Giordano et al, 2004;Miao et al, 2011;Shah et al, 2012;Kaushik et al, 2014) The average age at diagnosis in our population was 52 years with 7 of our patients falling in the age group 50 to 55. This was 5 years younger than the age of diagnosis of women with FBC in Pakistan.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations